PENGGUNAAN SLIDER (SLIDE AND LADDER) BOARD UNTUK MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS KELAS IV SDN KAWENGAN KEDEWAN - oktha ika rahmawati; Meiga Ratih Tirtanawati; Rika Pristian Fitri A (STKIP PGRI Sidoarjo, 2023)
English is a subject that is considered difficult by most elementary school students, especially students in the regions. Students' ability to remember vocabulary is one of the difficulties that is often encountered because English is a foreign language that we never use in everyday life. These difficulties can be overcome by using the right media in the learning process. One of the media that can be used is Snakes and ladders which in this service activity is modified into Slides and Ladder (slide and ladder). This media is made using the Canva application where in each box there are objects that must be answered by students. In the application of this media it can be seen that students are excited to take part in the games given. Students also seem motivated to try to answer the questions given in each box they step on. So it can be concluded that the use of appropriate media in learning can trigger students to be excited so that what they get can be embedded in students' long term memory.